Moralitas Perang: Tanggapan Gereja Katolik terhadap Perang - Bhakti, Angga Satya (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2015)
The current article intends to discuss that human being sees war as inevitable reality in life. When human being wants to survive, he/she will fight for his/ her life. Sometimes, war is considered to be the final way to survive. People make war as factual reality, but do they really want to fight in war? On the progress, people constitute rule of war or war ethics. A true rule is an embodiment of hope to prevent worse damages caused by war. Love is the prior value in living a humane life. Human being expects more love. Humankind have made many deals to avoid war as far as possible. War is not necessary if there is another stronger value to influence people’s life.